2019
DOI: 10.1007/s00259-019-04646-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PET imaging of PD-L1 expression in xenograft and syngeneic tumour models using a site-specifically labelled PD-L1 antibody

Abstract: Purpose Despite remarkable clinical responses and prolonged survival across several cancers, not all patients benefit from PD-1/ PD-L1 immune checkpoint blockade. Accordingly, assessment of tumour PD-L1 expression by immunohistochemistry (IHC) is increasingly applied to guide patient selection, therapeutic monitoring, and improve overall response rates. However, tissuebased methods are invasive and prone to sampling error. We therefore developed a PET radiotracer to specifically detect PD-L1 expression in a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…Similar results have been proven also by Christensen et al [ 70 ]. Authors studied the efficacy of the anti-PD-L1 (clone 6E11) conjugated with dibenzocyclooctyne-Desferrioxamine (DIBO-DFO) chelator and radiolabelled with [ 89 Zr] ([ 89 Zr]DFO-6E11) on NSCLC xenografts and syngeneic tumors models with different levels of PD-L1 in CT26 tumor-bearing mice subjected to external radiation therapy (XRT) in combination with PD-L1 blockade.…”
Section: Molecular Imagingsupporting
confidence: 92%
“…Similar results have been proven also by Christensen et al [ 70 ]. Authors studied the efficacy of the anti-PD-L1 (clone 6E11) conjugated with dibenzocyclooctyne-Desferrioxamine (DIBO-DFO) chelator and radiolabelled with [ 89 Zr] ([ 89 Zr]DFO-6E11) on NSCLC xenografts and syngeneic tumors models with different levels of PD-L1 in CT26 tumor-bearing mice subjected to external radiation therapy (XRT) in combination with PD-L1 blockade.…”
Section: Molecular Imagingsupporting
confidence: 92%
“…Molecular imaging comprehensively detects PD-L1 expression in patients with tumors throughout the body, and analyzes the real-time dynamic analysis of possible changes in tumor PD-L1 expression during treatment. So far, many studies have used different radionuclides, such as ( 99 mTc, 68 Ga, 64 Cu, 89 Zr, and 18 F) to label PD-L1 monoclonal antibodies [20,21] or engineered PD-L1specific peptides [22][23][24] in preclinical and clinical research. Some researchers have even found that atezolizumab labeled with 89 Zr can predict the PFS and OS in patients better than the IHC-based core needle biopsy [21].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular imaging comprehensively detects PD-L1 expression in patients with tumors throughout the body, and analyzes the real-time dynamic analysis of possible changes in tumor PD-L1 expression during treatment. So far, many studies have used different radionuclides, such as ( 99 mTc , 68 Ga, 64 Cu, 89 Zr and 18 F) to label PD-L1 monoclonal antibodies [19,20] or engineered PD-L1 specific peptides [21][22][23] in preclinical and clinical research. Some researchers have even found that atezolizumab labeled with 89 Zr can predict the PFS and OS in patients better than the IHC-based core needle biopsy [20].…”
Section: Discussionmentioning
confidence: 99%